Obesity and periodontitis are not associated in pregnant women. (12th August 2019) - Gomes‐Filho, Isaac S.; Batista, Josicélia Estrela Tuy; Trindade, Soraya Castro; Passos‐Soares, Johelle de Santana; Cerqueira, Eneida de Moraes Marcílio; Costa, Teresinha Silveira da; Figueiredo, Ana Claudia Morais Godoy; Costa, Maria da Conceição Nascimento; Adan, Luis Fernando Fernandes; Orrico, Gessica Santana; Porto, Edla Carvalho Lima; Pimenta, Rodolfo Macedo Cruz; et al.
Abstract: Objective: The objective of this study was to investigate an association between obesity (exposure) and periodontitis (outcome) in pregnant women. Background: This association was investigated and only five studies were identified as showing a positive association. However, some of these studies had limitations such as reduced sample sizes, inadequate exposure criteria and outcome measures, which question the internal validity of these investigations. Methods: A cross‐sectional study was carried out with a sample of 644 pregnant women of the public health service of the municipality of Santo Antônio de Jesus, Bahia, Brazil. Data were obtained by collecting of socioeconomic‐demographic information, health behavior, health conditions, and reproductive history through an interview. Obesity was evaluated using body mass index adjusted for gestational age and expected weight gain. The diagnosis of periodontitis followed two criteria: (a) Center for Disease Prevention and Control and American Academy of Periodontology (CDC/AAP); (b) Gomes‐Filho et al (2018) using criterion that also evaluated bleeding upon probing; Prevalence ratios and respective 95% confidence intervals were obtained by Poisson regression analysis. Results: In accordance with the outcome diagnostic criterion, the frequency of periodontitis was 17.24% (Gomes‐Filho et al) and 66.92% (CDC/AAP). The participants were classified as low weight (19.72%), adequate weight (42.39%), overweight (24.84%), and obesity (13.04%), based on the exposure diagnostic criterion. The low weight and overweight groups were excluded from the data analysis, giving a final sample of 357 pregnant women. The association between obesity in pregnant women and periodontitis was not statistically significant, after adjusting for confounders such as age, schooling level, alcoholic beverage consumption, alimentary and nutritional orientation, urinary infection, and dental flossing. Conclusions: The findings showed a high frequency of periodontitis, obesity, and overweight in the studied population but no association between obesity and periodontitis in pregnant women was found.